ANALISIS KELAYAKAN FINANSIAL ANGKUTAN TIRTAYATRA BALI - JAWA TIMUR - Suweda, I Wayan; Udiana Putra, I Gede Putu (JURNAL SPEKTRAN; Vol 7 No 1 (2019): Vol. 7, No.1, Januari 2019, 2019)
FINANCIAL ANALYSIS OF BALI-EAST JAVA TIRTAYATRA TRANSPORTATION   ABSTRACT   Bali, with its predominantly Hindu, has experienced a fairly rapid development of the tourism sector. With personal awareness and supported by the better economic condition, the Balinese Hindu people are able to religious travel ( tirtayatra ) to other areas. Travel Companies catch this opportunity by opening travel packages to several temples in East Java. This study aims to analyze the level of financial investment feasibility in the tirtayatra transportation business. Feasibility of investment can be obtained by comparing the variables of benefit and cost. Analysis of the level of feasibility is determined by applying the NPV, IRR and BCR methods and sensitivity analysis. Data used, both primary and secondary, are obtained from several Travel Companies in Bali. From the results it can be concluded that the investment of the Tirtayatra package Bali - East Java is a package that continues to grow. In the feasibility analysis that is served by 3 medium bus and the vehicles economic life of 7-year, the Present Value of benefit is Rp. 11,891,301,439 and the Present Value of cost is Rp. 11,335,305,821. Therefore, the result gives the value of NPV Rp.555,995,618 > 0, BCR = 1.0490 > 1 and IRR = 27.63% > i (17%). Thus the investment at religious travel can be considered feasible. However, this package will be inappropriate if the annual interest rate passes the value of 27.63%.